Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1957
DOI: 10.1038/bjc.1957.73
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Certain Proteins in Normal and Pathological Epidermis

Abstract: THE manner by which carcinogenic agents induce neoplastic growths is unknown in spite of the large amount of work which has been carried out on the chemistry of carcinogenesis. Epidermis was chosen as the tissue of choice for the work reported here for reasons given previously (Carruthers, 1950). Various stages in the malignant process such as methylcholanthrene-induced hyperplastic epidermis, papillomas and squamous-cell carcinomas were investigated. These phases were studied because large changes were sought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1963
1963
1978
1978

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…These ureaextracted proteins are extracted with 6 mol/l urea and precipitated maximally at pH (Carruthers et al, 1955(Carruthers et al, , 1957Rudall, 1.952), and are sometimes denoted as the urea-extractable 5-5 proteins; herein for simplicity they are called the urea proteins. Previous studies indicated that epidermis contained urea-extractable antigens which were absent, or present in small amounts, in carcinoma and that carcinoma contained urea-extractable antigens which were absent or present in small amounts in epidermis.…”
mentioning
confidence: 99%
“…These ureaextracted proteins are extracted with 6 mol/l urea and precipitated maximally at pH (Carruthers et al, 1955(Carruthers et al, , 1957Rudall, 1.952), and are sometimes denoted as the urea-extractable 5-5 proteins; herein for simplicity they are called the urea proteins. Previous studies indicated that epidermis contained urea-extractable antigens which were absent, or present in small amounts, in carcinoma and that carcinoma contained urea-extractable antigens which were absent or present in small amounts in epidermis.…”
mentioning
confidence: 99%
“…The 1 The author acknowledges the excellent technical assistance of Mrs. A. Heining and McKenna and Miss A. Baumler. C a r r u t h e r s urea-extractable or fibrous proteins [16] were solubilized from the related epidermal tissues with 6 m urea and were then isolated by precipitation at pH 5.5 [9,10,16]; they are designated herein simply as the urea proteins. In this report further evidence is submitted on the nature of the differences in the urea proteins of epidermis at various stages of neoplastic transfor mation.…”
Section: Introductionmentioning
confidence: 99%
“…Fractionation was accomplished by ~ltracentrifugation~ with a combination of previous methods (10,11) according to Scheme I. All Results are averages of thren?…”
mentioning
confidence: 99%